Месть командира: [роман] / Георгий Миронов - Миронов Георгий Ефимович (Черная кошка, 1996)
Экземпляры: ф-12 (20220411) / Инвентарный номер: 58129 / Цена: 40.00 / Сис.шифр: Р2 / Авт.знак: М 64 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6